The Relevance of Ihdad Regulations as a Sign of Mourning and Human Rights Restriction - Zaidah, Yusna; Raihanah Abdullah (Lembaga Contrarius Indonesia, 2024)
Ihdad is a form of mourning carried out by families. The sharia mandates ihdad for women who have lost their husbands. There is no fiqh regarding ihdad for husbands. It often gives rise to the perception that there is a tendency to discriminate against women. However, customary law has regulations for mourning periods for husbands. This article aims to determine the relevance of Islamic law in regulating the mourning period for women and men with the value of protecting human rights. The research was carried out normatively by comparing shariah, positive legal regulations in Indonesia, notably the customs of the Banjar community, and regulations in Malaysia. The theories underlying this research include customary law theory, al-maslahah, and human rights protection. The results of this research illustrate that Islamic fiqh does not regulate ihdad for husbands. In Indonesia, KHI regulates the mourning period (ihdad) not only for wives but also for husbands. Meanwhile, in Malaysia, there is no ihdad for husbands, and the rules are explicit in the Enactment of the Islamic Family Law. The customary law of the Banjar community regulates the mourning period for the husband by not remarrying and not interfering with inheritance matters during the mourning period for a period of one hundred days. Customary laws that do not conflict with sharia and meet the requirements for implementing 'urf can be implemented. Ihdad is and will continue to be relevant to protecting human rights by prioritizing the values of maslahah and respect. The rules in Indonesia and Malaysia are based on Islamic law, considering religious and humanist values in the form of leniency.